Natural Killer Cells Mediate Long-term Kidney Allograft Injury. Issue 5 (May 2015) - Zhang, Zhu-Xu; Huang, Xuyan; Jiang, Jifu; Lau, Arthur; Yin, Ziqin; Liu, Weihua; Haig, Aaron; Jevnikar, Anthony M.
Abstract : Background: Chronic allograft injury remains the leading cause of late kidney graft loss despite improvements in immunosuppressive drugs and a reduction in acute T cell–mediated rejection. We have recently demonstrated that natural killer (NK) cells are cytotoxic to tubular epithelial cells and contribute to acute kidney ischemia-reperfusion injury. The role of NK cells in kidney allograft rejection has not been studied. Methods: A "parent to F1" kidney transplant model was used to study NK cell–mediated transplant rejection. Results: The C57BL/6 kidneys were transplanted into fully nephrectomized CB6F1 (C57BL/6 x BALB/c) mice. Serum creatinine levels increased from baseline (18.8 ± 5.0 μmol/L to 37.2 ± 5.9 μmol/L, P < 0.001) at 60 days after transplantation. B6Rag −/− -to-CB6F1Rag −/− (B6Rag −/− xBALB/cRag −/− ) recipients, which lack T and B cells but retain NK cells, showed similar levels of kidney dysfunction 65 days after transplantation (creatinine, 33.8 ± 7.9 μmol/L vs 17.5 ± 5.1 μmol/L in nontransplant Rag −/− mice, P < 0.05). Importantly, depletion of NK cells in Rag1 −/− recipients inhibited kidney injury (24.6 ± 5.5 μmol/L, P < 0.05). Osteopontin, which can activate NK cells to mediate tubular epithelial cell death in vitro, was highly expressed in 60 days kidney grafts. Osteopontin null kidney grafts had reduced injury after transplantation into CB6F1 mice (17.7 ± 3.1 μmol/L, P < 0.001). Conclusions: Collectively, these data demonstrate for the first time that independent of T and B cells, NK cells have a critical role in mediating long-term transplant kidney injury. Specific therapeutic strategies that target NK cells in addition to conventional immunosuppression may be required to attenuate chronic kidney transplant injury. Abstract : The role of natural killer (NK) cells during rejection remains unclear. This elegant study dissects the role of NK cells during long-term graft survival.